DOI: 10.36443/10259/142
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la quimioterapia antineoplásica en pacientes con cáncer colorrectal sobre biomarcadores del estrés oxidativo y del estado redox plasmático

Abstract: en pacientes con cáncer colorrectal………………………………….. Estudio del estrés oxidativo en pacientes con cáncercolorrectal asociado al tratamiento quimioterápico……………..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 285 publications
(347 reference statements)
0
4
0
Order By: Relevance
“…Beside enzymes, other molecules can also act as antioxidants, such as NADPH, GSH and different vitamins, among other molecules [ 14 , 15 , 16 ]. Despite this antioxidant system, an excessive production of ROS can lead to an oxidative stress situation inducing several types of damage to different biomolecules [ 17 ]. In cancer processes, an excessive production of ROS has been related to genomic instability due to the induction of DNA damage and to the alterations in signaling pathways involved in survival, proliferation and apoptosis resistance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Beside enzymes, other molecules can also act as antioxidants, such as NADPH, GSH and different vitamins, among other molecules [ 14 , 15 , 16 ]. Despite this antioxidant system, an excessive production of ROS can lead to an oxidative stress situation inducing several types of damage to different biomolecules [ 17 ]. In cancer processes, an excessive production of ROS has been related to genomic instability due to the induction of DNA damage and to the alterations in signaling pathways involved in survival, proliferation and apoptosis resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer processes, an excessive production of ROS has been related to genomic instability due to the induction of DNA damage and to the alterations in signaling pathways involved in survival, proliferation and apoptosis resistance. Moreover, it has been demonstrated that ROS induce vascular endothelial growth factor (VEGF) expression, producing neovascularization and fast expansion of the cancer, modifying angiogenesis and metastasis, which induce the malignancy of cancer cells [ 17 ]. The use of natural compounds with antioxidant capacity that reduce ROS levels could decrease metastatic progression [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations